ANALISIS PENGARUH PERLAKUAN PANAS HASIL PENGELASAN GMAW BAJA ST - 40 TERHADAP KEKERASAN DAN STRUKTUR MIKRO - Muhammad Ikhwanul Munir; Priyagung Hartono; Artono Raharjo (RING ME, 2023)
ABSTRACT Currently, many welding elements are involved in construction, especially in the field of design, because welding is one way of making connections, and to obtain good quality connections requires the skills of technically advanced welders. One welding method that is often used in the manufacturing industry is Gas Metal Arc Welding (GMAW). This welding uses noble gases and carbon dioxide gas as a shield for the arc and molten metal from atmospheric influences. After testing the micro Rockwell hardness and micro structure, data was obtained that could be analyzed further. In this study, the material was ST 40 steel with a thickness of 10 mm, welding was carried out using GMAW welding with butt join welding and 1G position. Hardness testing uses the micro rockwell method at each time variation of 60 minutes, 90 minutes and 120 minutes at the Weld metal point and HAZ (Heat Affected Zone) with a maximum load of 650 g. Micro Rockwell hardness test results from the three time variations, the highest hardness value was found in welding with a time of 120 minutes with a value for weld metal of 71.3 HRN and a HAZ of 62.3 HRN. The lowest hardness value was found in welding using a time of 60 minutes with a value for weld metal of 68.6 HRN and HAZ of 59.1 HRN. Keywords: GMAW Welding, Rockwell Hardness, Microstructure